Addressing COVID-19 Among People Experiencing Homelessness: Description, Adaptation, and Early Findings of a Multiagency Response in Boston. (July 2020) - Baggett, Travis P.; Racine, Melanie W.; Lewis, Elizabeth; De Las Nueces, Denise; O'Connell, James J.; Bock, Barry; Gaeta, Jessie M.
People experiencing homelessness are at high risk for coronavirus disease 2019 (COVID-19). In March 2020, Boston Health Care for the Homeless Program, in partnership with city and state public health agencies, municipal leaders, and homeless service providers, developed and implemented a citywide COVID-19 care model for this vulnerable population. Components included symptom screening at shelter front doors, expedited testing at pop-up sites, isolation and management venues for symptomatic people under investigation and for people with confirmed disease, quarantine venues for asymptomatic exposed people, and contact investigation and tracing. Real-time disease surveillance efforts in a large shelter outbreak of COVID-19 during the third week of operations illustrated the need for several adaptations to the care model to better respond to the local epidemiology of illness among people experiencing homelessness. Symptom screening was de-emphasized given the high number of asymptomatic or minimally symptomatic infections discovered during mass testing; contact tracing and quarantining were phased out under the assumption of universal exposure among the sheltered population; and isolation and management venues were rapidly expanded to accommodate a surge in people with newly diagnosed COVID-19. During the first 6 weeks of operation, 429 of 1297 (33.1%) tested people were positive for COVID-19; of these, 395 people were experiencing homelessness at the time of testing, representing about 10% of the homeless adult population in Boston. Universal testing, as resources permit, is a focal point of ongoing efforts to mitigate the effect of COVID-19 on this vulnerable group of people.